Geografsko vrednotenje degradiranih območij v izbranih statističnih regijah - Cvahte, Anja (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2011)
Brownfields are inadequately exploited parts of landscape which could, with proper organization and management, present a potential for sustainable use. Auniform, complete and up-to-date record of brownfields is the initial phase in achieving this goal. The paper presents identification, inventory and geographical evaluation of brownfields in selected statistical regions of Gorenjska, Osrednjeslovenska, Spodnjeposavska, Zasavska and Jugovzhodna Slovenija.
Keywords: degradirana območja; environmental protection; landscape ecology; pokrajinska ekologija; protected areas; Slovenia; Slovenija; sonaravni razvoj; sustainable development; trajnostni razvoj; varstvo okolja; zavarovana območja